The Effect of Additional Feed Fermentation of Moringa Oleifera Leaves on The Cholesterol Level of Mojosari Laying Ducks - Lestari, Ratna Dwi; Lokapirnasari, Widya Paramita; Al Arif, Muhammad Anam; Hidanah, Sri; Soeharsono, Soeharsono; Lamid, Mirni (Universitas Airlangga, 2021)
The purpose of this research was to determine the effect of supplementary feeding with fermented Moringa leaf flour on cholesterol levels of Mojosari duck eggs and to calculate the cost of production. This study used 60 mojosari ducks, layer phase aged 27 weeks. Moringa flour was fermented using probiotics and given in four treatments, namely P0 (100% commercial feed), P1 (0.5% moringa leaf flour fermentation + 100% commercial feed), P2 (1% moringa leaf flour fermentation + 100% commercial feed), P3 (1.5% fermented Moringa leaf meal + 100% commercial feed). The variable observed in this study was cholesterol levels in Mojosari duck eggs. The results showed thatgiving Moringa leaf flour fermentation can give significantly different values (p <0.05) in each treatment both P0, P1, P2 and P3.In the fermentation of moringa leaf flour as much as 1.5% (P3) had the lowest cholesterol levels (113.13 ± 12.55) Meanwhile, 1% (P2) of moringa leaf flour fermentation has the highest cholesterol level (170.42 ± 13.19).